Heavily Indebted Poor Countries Initiative and Multilateral Debt Relief Initiative : Statistical Update. (Policy Papers; Policy Paper, 2013)
This report provides an update on the status of implementation of the HIPC Initiative and the MDRI over the past year. Given that most HIPCs have reached the completion point, in November 2011, the IMF and IDA Boards2 endorsed staff's proposal to further streamline reporting of progress under the HIPC Initiative and MDRI. It was agreed that the annual HIPC Initiative/MDRI status of implementation report will be discontinued, while the core information-on debt service and poverty reducing expenditure, the cost of debt relief, creditor participation rates, and litigation against HIPCs-should continue to be made available and updated regularly on the IMF and World Bank websites.